2018
DOI: 10.1136/bjophthalmol-2017-311803
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of avoidable blindness and diabetic retinopathy in people aged 50 years and older in the National Capital District of Papua New Guinea

Abstract: Prevalence of diabetes in adults aged 50 years and older was lower than reported elsewhere in the region, and lower than other RAAB+DR surveys. Despite this, the prevalence of DR is high compared with other RAAB+DR surveys and demonstrates the need for increased awareness and accessibility to eye services for people with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…A low proportion of the participants (3.9%) was known patients with DM, and 71.4% knew the effect of DM on the eyes. In a previous study in PNG, Burnett et al [ 13 ] estimated the prevalence of DM as 8.1% which was higher compared to this study. The difference can be attributed to the age range involved in both studies.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…A low proportion of the participants (3.9%) was known patients with DM, and 71.4% knew the effect of DM on the eyes. In a previous study in PNG, Burnett et al [ 13 ] estimated the prevalence of DM as 8.1% which was higher compared to this study. The difference can be attributed to the age range involved in both studies.…”
Section: Discussioncontrasting
confidence: 69%
“…They reported that even though oral hypoglycaemic drugs and insulin were mostly available in hospitals, there was inadequate trained DM professionals such as endocrinologists and dieticians. Most recently, in 2017, a study was conducted by Burnett et al [ 13 ] to assess the prevalence of DM and DR in PNG. The study estimated the prevalence of DM to be 8.1% out of which 62.5% were undiagnosed prior to the study.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the RAAB showed that the prevalence of blindness was 5.6% and that the two most common causes of avoidable blindness in PNG were cataracts and uncorrected refractive errors. 5 In the Highlands the prevalence of blindness was shown to be 11.1% in females. 5 Perhaps unsurprisingly, lack of awareness is a general barrier to treatment, particularly for women.…”
Section: Challengesmentioning
confidence: 99%
“… 5 In the Highlands the prevalence of blindness was shown to be 11.1% in females. 5 Perhaps unsurprisingly, lack of awareness is a general barrier to treatment, particularly for women. More than 45 000 people in PNG are avoidably blind and there is also an unacceptable backlog of unoperated cataracts is how it would be referred to in PNG.…”
Section: Challengesmentioning
confidence: 99%
“…In 2017, Burnett et al [21] indicated that the prevalence of DR and/or maculopathy in people aged 50 years and above in the National Capital District of Papua New Guinea (PNG) was 46.4%. e rapid assessment of avoidable blindness study also identified posterior segment diseases, DR, and AMD as principal causes of visual impairment and blindness in PNG [22].…”
Section: Introductionmentioning
confidence: 99%